Skarga pokrzywdzonego męża – edycja XVII-wiecznej mowy sejmikowej - Anita Londzin (Meluzyna: dawna literatura i kultura)
The work includes an edition of the speech of the sejmik preserved in the manuscript of Andrzej Lubieniecki (copy of the Remonstrantów Library 527). The author’s goal was a comprehensive rhetorical analysis of the text, possible thanks to the recognition of the unusual circumstances of the case itself. This document is valuable from the point of view of researchers of Old Polish linguistic culture.